Training on Preparing Physical Condition Test Instruments for Pb Badminton Athletes. Brilliant - Yundarwati, Susi; Soemardiawan, Soemardiawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The expected goal is to create trainers who have knowledge about training in preparing physical condition test instruments for PB badminton athletes. Gemilang understands the importance of the physical condition components of badminton in Mataram. improve the performance of all Mataram City athletes effectively, efficiently and modernly. Mitra's problem is that the trainers lack knowledge regarding training in preparing physical condition test instruments for PB badminton athletes. Glorious, and many trainers still carry out conventional physical conditions without using sports science technology that is developing in the field of sports. The urgency of the problem is that there are no guidelines for the physical condition test instruments used by PB. The Glorious City of Mataram, is only conventional, not programmed to be varied, effective, the coach's experience of being an athlete is not the solution that is obtained. The solution method is by holding socialization, training, mentoring and evaluation analysis. Training on preparing physical condition test instruments for PB badminton athletes. A good performance according to this branch of sport. So that the training guidelines for preparing test instruments can be used as a basis for coaches to determine the physical condition of Badminton athletes. It is hoped that the results of the training service research will allow coaches to develop test instruments and measure physical conditions as reference material in formulating training programs so that they can improve the performance of badminton athletes. The conclusion is that there is knowledge about training in preparing physical condition test instruments for PB badminton athletes. Brilliant. provide a significant impact on systematic physical condition tests, effectively and efficiently to improve the performance of Mataram badminton athletes.